2012
DOI: 10.1590/s2176-94512012000200022
|View full text |Cite
|
Sign up to set email alerts
|

Photometric study of divine proportion and its correlation with facial attractiveness

Abstract: Objective: The aim of this study was to evaluate if there is correlation between perception of facial esthetic and divine proportion, verifying if most attractive faces are closer to and less attractive faces are more distant to this proportion. Methods:Standard facial photographs (frontal and lateral) in natural head position were taken of a sample of 85 Brazilian Caucasian women, with mean age of 23 years and 9 months. The photographs were evaluated by 5 orthodontists, 5 artists and 5 laymen and were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Regarding the face, similarly to many other values derived from anthropometric studies, φ can be found in and is regarded as compatible with subjectively pleasant proportions . The golden section can be involved in the esthetics of a face to a certain extent, but a visually unusual result is obtained if a face is completely built with such proportions . The definition of beauty is extremely complex; in particular it is difficult to determine whether we objectively find φ in subjectively beautiful faces or if these faces are considered beautiful because of an alchemy of proportions, with φ as a component …”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Regarding the face, similarly to many other values derived from anthropometric studies, φ can be found in and is regarded as compatible with subjectively pleasant proportions . The golden section can be involved in the esthetics of a face to a certain extent, but a visually unusual result is obtained if a face is completely built with such proportions . The definition of beauty is extremely complex; in particular it is difficult to determine whether we objectively find φ in subjectively beautiful faces or if these faces are considered beautiful because of an alchemy of proportions, with φ as a component …”
Section: Introductionmentioning
confidence: 89%
“…The face was ideally positioned in an orthonormal coordinate system with 3 planes of symmetry: the orbital plane, the midsagittal plane and the Frankfort horizontal plane. The landmarks used in this study were based on Farkas' definitions . Measurements were taken in the true vertical plane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the validity of these putative rules is still in question. Recent studies have shown that the most attractive ratios are not exactly golden ratio [Holland 2008;Peron et al 2012]. Fan et al [2012] generated a synthesized face image that has neoclassical canons and the most possible golden ratios, but it only received a below normal rating.…”
Section: Introductionmentioning
confidence: 99%